Outcome of Keratoconus Management: Review of the Past 20 Years' Contemporary Treatment Modalities. Issue 3 (May 2017) - Mandathara, Preeji S.; Stapleton, Fiona J.; Willcox, Mark D. P.
Abstract : Objectives: To describe the past 20 years' contemporary management modalities for keratoconus (KC) and their outcomes and failures and to propose recommendations in reporting their outcomes. Methods: A systematic review of the literature on KC management options for the last 20 years was performed. Original articles that reported the outcome of any form of KC management other than full-thickness or lamellar corneal graft were reviewed to collect information on their outcomes and complications and the level of scientific evidence of the study. Results: A total of 1, 147 articles retrieved and of those, 241 satisfied the inclusion criteria, and 41.1% of them were prospective case series. The higher level of evidence studies, that is, randomized controlled trials (RCTs), were limited to only one intervention, that is, corneal collagen cross-linking (CXL). However, the quality of most RCTs was limited because of performance and detection bias. Contact lenses (CLs) remain the mainstream of KC management and were associated with reversible and non–sight-threatening complications. Surgical options such as intracorneal segment implantation and phakic intraocular lens are considered in the visual rehabilitation of CL intolerants, and CXL is the only available option to stop or delay the disease progression. Generally, these surgical procedures are associated with transient inflammatory events and permanent sequelae. Conclusions: The published studies on KC management options varied significantly with respect to the study population, age of participants, severity of KC, clinical outcome measurements, and follow-up period. High-quality longer follow-up RCTs are required to evaluate the long-term effects of KC interventions.